Juridical review of the execution of debtor's fiduciary collateral objects in default - Adawiyah, Rodiatun; Prasetyo, Muhammad Arif; Ayu, Hanuring; Lifistio, Alfredo; Lietanto, Sandiego; Michael, Michael; Anwi, Marco (Priviet Social Sciences Journal, 2022)
Fiduciary is a process of transferring ownership rights to an object based on trust with the provision that the object whose ownership rights are transferred remains in the power of the object owner. As for fiduciary guarantees, which are guarantees for the rights of tangible or intangible movable objects, immovable objects such as buildings. In this case, the building cannot be subject to mortgages as stated in Law Number 04 of 11996 concerning mortgages which are stated to remain in the power of the fiduciary giver as collateral for the settlement of certain debts, where the priority position is the fiduciary recipientx against other creditors. On this occasion, the author will discuss a discussion entitled, “Juridical Review of the Execution of Guarantees x Fiduciary x Debtors x Defaults”. In this discussion, the research methodx that is usedx to fulfill related material is the normative legal research methodx which uses data collection techniques from written sources such as books and heritage studies as well as other supporting sources. Looking at the title, it is conveyed regarding the execution of fiduciary guarantees, where this can be done if the debtor or fiduciary giver deviates from the promise, in this case the execution is carried out by implementing executorial title as stated in Article v15vayat2. As for what is stated regarding the sale of xobjects that are objects of fiduciary guarantees for the power of fiduciary recipients through general customers. Sales proceeds are obtained by obtaining the highest price so that it will benefit both parties based on applicable law. The purpose of writing this journal is to know the procedure for executing fiduciary collateral objects, to find out whether creditors can transfer the ownership rights of collateral objects to third parties, to find out whether debtors can transfer property rights to collateral objects during the guarantee period, to know the role of the police in securing the execution of fiduciary collateral objects